27c+38cdg=

Simple and best practice solution for 27c+38cdg= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27c+38cdg= equation:


Simplifying
27c + 38cdg = 0

Solving
27c + 38cdg = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'c'.
c(27 + 38dg) = 0

Subproblem 1

Set the factor 'c' equal to zero and attempt to solve: Simplifying c = 0 Solving c = 0 Move all terms containing c to the left, all other terms to the right. Simplifying c = 0

Subproblem 2

Set the factor '(27 + 38dg)' equal to zero and attempt to solve: Simplifying 27 + 38dg = 0 Solving 27 + 38dg = 0 Move all terms containing c to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 38dg = 0 + -27 Combine like terms: 27 + -27 = 0 0 + 38dg = 0 + -27 38dg = 0 + -27 Combine like terms: 0 + -27 = -27 38dg = -27 Add '-38dg' to each side of the equation. 38dg + -38dg = -27 + -38dg Combine like terms: 38dg + -38dg = 0 0 = -27 + -38dg Simplifying 0 = -27 + -38dg The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

c = {0}

You can always share this solution

See similar equations:

| 6d+5d-d-10d= | | 3BC-BC+10BC-7BC= | | 3x+9= | | 6qr+3q= | | 6x+3= | | u+UV+4UV= | | 3y^2-2y-8=0 | | 11y-15=(y+5)(y-3) | | 10n+2p-p= | | 8q+10q-5q= | | 5a+2b=8 | | 7x+4=y | | -8d+4d+-2d+8= | | 27hjk+46km-17hjk-46km= | | (2x-3)(x+8)=(x-4)(x+6) | | 0.4(10+5x)=2x | | x+7y=19 | | 4x=512 | | 2x^2-28x=-3x^2-2x-24 | | 5x^2+8x-10=6-8x | | 10g-4g+4g+6g= | | 8y=10y^2 | | 8y=1-y^2 | | 8x-3x+4=9-2+5x | | x^2+20x+100=0 | | 6x^2-10x-44=0 | | 8+5tu= | | 2x=128 | | 30x^2-11x-30=0 | | 8+20x=20x+8 | | x^2-21=-4x | | 2(3n+7)=8 | | 25x^2-9=0 | | 4d+4dg-d= | | 5(x-7)=7 | | 60x^3-20x^2-5x=0 | | (9x-7)(81x^2-126x+49)=0 | | 2*3x-2(x+1)=0.7 | | 2*3x-2(x+1)=.7 | | 7x+3=4x+12 | | 10x^2+78x=16 | | 4(2+5x)=20x+8 | | x(6x-7)=13 | | (x+2)(x-3)=4x | | (3x-8)(6x+5)=0 | | (8x+9)(4x-7)=0 | | x+5.2=-18.73 | | (36)(y)=14.76 | | 4.58+v=2.5 | | 8965=4 | | 11x=166 | | 3x+4=11x-6 | | 5523=0 | | 0=1111 | | 0+0=7777 | | 3y+2x=z | | 4x+9=-2x-6 | | r^2=54-3r | | -[3x+(9x+7)]=6-(3x+9) | | 10d+2dg-6d+5d-2dg= | | 2s-s+7s= | | 2x*2x+1*1-3x=5 | | 10qr-3qr+6qr-3qr= | | 14x^3+10x^2+6x= | | 2j-j+9j= |

Equations solver categories